Revision of Chalcedectidae (Hymenoptera, Chalcidoidea) from the Afrotropical, Oriental and Palaearctic regions with description of eleven new species - van Noort, Simon; Gibson, Gary A.p.; Ranjith, A.p.; Mitroiu, Mircea-Dan (Zootaxa, 2026)
The family Chalcedectidae (Hymenoptera: Chalcidoidea) is currently represented by described species in the Australasian, Nearctic, Neotropical and Palaearctic regions. We here extend the distribution of the family to the Afrotropical and Oriental regions with description of 11 new species, which represents a 50% increase in the number of described world species. Chalcedectus tankwa van Noort & Mitroiu, sp. nov., is newly described from the Afrotropical and Palaearctic regions based on both sexes, whereas C. copelandi Gibson & van Noort, sp. nov., is described from the Afrotropical region based on both sexes and provisionally recorded from the Palaearctic region based on males. Also newly described from the Afrotropical region are C. bisculpturatus Gibson, sp. nov. (female), C. mabeabai van Noort, sp. nov. (female), C. madagascarensis Gibson, sp. nov. (both sexes), and C. schroderae van Noort, sp. nov. (both sexes). Newly described from the Oriental region based on both sexes are C. atratus Gibson, sp. nov., C. indraneela Ranjith, sp. nov., C. peculiatergalis Ranjith & Gibson, sp. nov., C. prolixus Gibson, sp. nov., and C. striolatus Gibson, sp. nov. The two species previously described from the Palaearctic, C. balachowskyi Steffan and C. sinaiticus (Masi), are also treated. All species are imaged through macrophotography and keyed separately for the three regions treated. Online Lucid identification keys and images of all the species treated herein are available at: www.waspweb.org.